Association of gallbladder carcinoma with gallstone and its prevalence in a tertiary care teaching hospital (Mediscope, 2021)
Objective: To see the association of gallstones with gallbladder carcinoma and its prevalence in patients undergoing surgery for cholelithiasis.Methods: This cross-sectional observational study was conducted from July 2012 to June 2013 at the Department of Surgery, Mymensingh Medical College Hospital, Mymensingh with 150 cases of cholelithiasis.Results: Of 150 cases those were operated for gall bladder stone disease, 8 (eight) were found to have carcinoma of gall bladder i.e. prevalence was 5.3%. On ultrasound, only three (37.5%) patients were suspected as gall bladder carcinoma pre-operatively. Females are more affected than males by this disease. Also gall bladder carcinoma was found to be associated with single large-sized stone.Conclusion: The ultrasonography can miss a significant number of malignant lesions of the gall bladder in early stages and every cholecystectomy specimen should be examined histologically.Mediscope 2021;8(2): 87-93